De-novo identification of specific exposure biomarkers of the alternative plasticizer di(2-ethylhexyl) terephthalate (DEHTP) after low oral dosage to male volunteers by HPLC-Q-Orbitrap-MS. (17th February 2018) - Lessmann, Frederik; Bury, Daniel; Weiss, Tobias; Hayen, Heiko; Brüning, Thomas; Koch, Holger M.
Abstract: Context: Human exposure biomonitoring relies on the availability of specific, sensitive biomarkers. For emerging chemicals, the identification (prediction, synthesis, verification) of such biomarkers is time and cost intensive. Objective: This study aimed to further elucidate the urinary metabolic profile of the plasticizer di(2-ethylhexyl) terephthalate (DEHTP) in search of probably additional biomarkers of exposure. Materials and methods: Urine samples of an oral low-dose volunteer study were analysed by HPLC-Q-Orbitrap-MS combined with a commercial data mining software. Metabolite identification was based on isotopic pattern, accurate masses of product ions and excretion profiles. Results: Nine phase I metabolites of DEHTP were tentatively identified by HPLC-Q-Orbitrap-MS. Four previously described, side chain oxidized monoester metabolites were confirmed in all samples. In addition, five previously unknown downstream metabolites were tentatively identified. Discussion and conclusion: The excretion profiles obtained by HPLC-Q-Orbitrap-MS were in good agreement with quantitative HPLC-QqQ-MS data. For the newly discovered metabolites, plausible excretion profiles, similar to the ones of the known metabolites, were obtained. The presented approach proved to be successful for metabolite screening in urine samples after low-dose exposure and will be applied in future human metabolism studies for a fast, reliable and cost effective identification of specific biomarkers of exposure.